Grasping the Revolution: Fieldwork on Religion in China - Lang, Graeme (Fieldwork in religion, 2005)
Field research on religion in China cannot easily test sociological theories because of the constraints on investigation and the sensitivity of some topics. But the rapid resurgence of religions in China over the past 20 years provides many settings for fieldwork, and theoretical revolutions in the discipline in recent decades create analytical challenges. We have been most impressed by the usefulness of the religious economy model. We have found good empirical and theoretical reasons to use it in the study of the resurgence of religious activity in China over the past 20 years. But fieldwork in China also brings surprises, and it is difficult to study some phenomena without also influencing them in unexpected ways. We illustrate the relation between fieldwork, theory, and surprises, with example.